1997
DOI: 10.1074/jbc.272.30.18752
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dihydropyridine Receptor Site ofl-type Calcium Channels by Alanine-scanning Mutagenesis

Abstract: antagonist PN200-110 by 2-25-fold. Both amino acid residues conserved among Ca 2؉ channels and those specific to L-type Ca 2؉ channels were found to be required for high affinity dihydropyridine binding. In addition, mutation F1462A increased the affinity for the dihydropyridine Ca 2؉ antagonist PN200-110 by 416-fold with no effect on the affinity for the Ca 2؉ agonist Bay K8644. The residues in transmembrane segments IIIS6 and IVS6 that are required for high affinity binding are primarily aligned on single fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 56 publications
4
94
0
Order By: Relevance
“…These include local anesthetics, class I antiarrhythmics and anticonvulsants that block Na ϩ channels, and dihydropyridines and phenylalkamines that block L-type Ca 2ϩ channels. For both channel types, molecular determinants for high-affinity drug binding have been identified in the S6 regions of domains III and IV by using Ala-scanning mutagenesis (27)(28)(29)(30). Although the drug binding sites are highly complex, there are some similarities with the binding site in HERG.…”
Section: Resultsmentioning
confidence: 99%
“…These include local anesthetics, class I antiarrhythmics and anticonvulsants that block Na ϩ channels, and dihydropyridines and phenylalkamines that block L-type Ca 2ϩ channels. For both channel types, molecular determinants for high-affinity drug binding have been identified in the S6 regions of domains III and IV by using Ala-scanning mutagenesis (27)(28)(29)(30). Although the drug binding sites are highly complex, there are some similarities with the binding site in HERG.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore we conclude that nifedipine is blocking L-type Ca 2ϩ channels found in the plasma membrane, with minor inhibitory effects at higher concentrations on Ca 2ϩ release from intracellular stores. Although the specificity of action of DHPs has been confirmed by determining the DHP binding sites on the channelforming ␣ 1 -subunit of L-type VDCCs (39,40), there are studies demonstrating the nonspecific inhibitory effects of high micromolar concentrations of DHPs on voltage-dependent potassium (K v ) channels and Ca 2ϩ -activated potassium (K ϩ ) channels (41)(42)(43). Even though these observations could be of concern in the present study, Fagni et al (42) reported that micromolar concentrations of both nifedipine and the stereospecific enantiomers of Bay K 8644 exhibited an inhibitory effect on K ϩ current through Kv and Ca 2ϩ -activated K ϩ channels.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the direct action of estrogen on L-type Cav1.2, we assessed the action of 17␤-E2 in HEK293 cells transiently cotransfected with the pore-forming subunit Cav1.2 and the accessory ␤1b and ␣2␦ subunits and GFP expression plasmids. HEK293 cells do not endogenously express either L-type VGCC or estrogen receptors (30,31). Transfected HEK cells (GFP positive) showed the expected Ca 2ϩ current activated in response to the same depolarizing protocol (Fig.…”
Section: Estrogen Action On L-type Vgcc Does Not Require Classical Esmentioning
confidence: 99%